2010
DOI: 10.3399/bjgp10x501859
|View full text |Cite
|
Sign up to set email alerts
|

Value for money and the Quality and Outcomes Framework in primary care in the UK NHS

Abstract: The Quality and Outcomes Framework (QOF) is a pioneering attempt to improve the quality of primary care in the UK through the use of financial rewards. Despite its achievements, there are concerns that the QOF may offer poor value for money. AimTo assess the cost-effectiveness of QOF payments. Design of studyEconomic analysis. SettingEngland, UK. MethodCost-effectiveness evidence was identified for a subset of nine QOF indicators with a direct therapeutic impact. These data were then applied to an analytic fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 16 publications
1
64
0
Order By: Relevance
“…We identified one prospective cohort, 9 two retrospective cohort, 10,11 and one pre-post study, 12 six cross-sectional surveys, [13][14][15][16][17] one economic analysis, 18 and two simulation studies. 19,20 Related to measure development, studies found that an emphasis on clinical quality and patient experience criteria was related to increased coordination of care, improved office staff interaction, and provider confidence in providing highquality care.…”
Section: Program Design Features (13 Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…We identified one prospective cohort, 9 two retrospective cohort, 10,11 and one pre-post study, 12 six cross-sectional surveys, [13][14][15][16][17] one economic analysis, 18 and two simulation studies. 19,20 Related to measure development, studies found that an emphasis on clinical quality and patient experience criteria was related to increased coordination of care, improved office staff interaction, and provider confidence in providing highquality care.…”
Section: Program Design Features (13 Studies)mentioning
confidence: 99%
“…Thirteen studies [9][10][11][12][13][14][15][16][17][18][19][20]50 examined program design features and found:…”
Section: Program Design Featuresmentioning
confidence: 99%
“…The Quality and Outcomes Framework incentive payments were found to be a cost-effective use of resources in the UK NHS primary care practices (Walker et al, 2010).…”
Section: Incentivizing and Rewarding Research Staffmentioning
confidence: 99%
“…Preliminary findings on cost-effectiveness for the QOF are also encouraging. 30 However, qualitative research has shown that the patient's agenda may be under threat due to the requirements to meet QOF targets and that there may be a divergence of opinion in relation to the worth of some aspects of care between general practice health professionals and patients. 31 We must strike a balance between the present chronic disease-focused elements of the QOF and the quality of patient-centred, humanitarian care that are more difficult to assess, but no less important.…”
Section: Effective Carementioning
confidence: 99%